A Practical and Stereoselective Organocatalytic Alkylation of Aldehydes with Benzodithiolylium Tetrafluoroborate. Issue 10 (17th March 2014) - Gualandi, Andrea; Mengozzi, Luca; Giacoboni, Jessica; Saulnier, Steve; Ciardi, Moira; Cozzi, Pier Giorgio
ABSTRACT Recently, the direct substitution of allylic, benzylic, and tertiary alcohols has been achieved via SN1‐type reactions with catalytic amounts of Brønsted or Lewis acids. When a new stereogenic center is formed most of these transformations produce the desired product as a racemate, as these reactions proceed through carbenium ions. The arsenal of activation modes available in organocatalysis can be used to set up suitable reaction conditions in which chiral nucleophiles (enamine catalysis) or chiral electrophiles (iminium catalysis, chiral counterion catalysis) can easily be generated. Recently, we have used stabilized carbenium ions, directly available or obtained from the corresponding alcohols, in new organocatalytic stereoselective SN1‐type reactions. The commercially available carbenium ion benzodithiolylium tetrafluoroborate 1 can be used for the straightforward organocatalytic stereoselectivealkylation of aldehydes. In this account we will illustrate the application of this methodology in the total synthesis of natural products and the preparation of valuable starting materials. Chirality 26:607–613, 2014. © 2014 Wiley Periodicals, Inc.